Fundamental principles of the Kyiv School District existence during the period of 1833-1834. Decrees of the Emperor and Сirculars of the Minister of Public Education (based on the «Journal of the Ministry of National enlightenment») - Кільова, Ганна Олексіївна (Pedagogy of Higher and Secondary Education, 2013)
Kilyova G. О. Fundamental principles of the Kyiv School District existence during the period of 1833-1834. Decrees of the Emperor and Сirculars of the Minister of Public Education (based on the «Journal of the Ministry of National enlightenment»). The article considers the functioning of the Kiev school district and most relevant government documents in this regard that define its system. These include the decrees of the emperor, the orders of the Minister of Public Education, circulars of Kiev school district trustee. The main focus is on the first two ones, that formed the principles of the school district, determined the main criteria of its development.